Weights of wild Mallard Anas platyrhynchos, Gadwall A. strepera, and Blue-winged Teal A. discors during the breeding season - Lokemoen, John T; Johnson, Douglas H; Sharp, David E (Wildfowl, 1990)
During 1976-81 we weighed several thousands of wild Mallard, Gadwall, and Blue-winged Teal in central North Dakota to examine duckling growth patterns, adult weights, and the factors influencing them. One-day-old Mallard and Gadwall averaged 32.4 and 30.4 g, respectively, a reduction of 34% and 29% from fresh egg weights. In all three species, the logistic growth curve provided a good fit for duckling growth patterns. Except for the asymptote, there was no difference in growth curves between males and females of a species. Mallard and Gadwall ducklings were heavier in years when wetland area was extensive or had increased from the previous year. Weights of after-second-year females were greater than yearlings for Mallard but not for Gadwall or Blue-winged Teal. Adult mallard females lost weight continuously from late March to early July. Gadwall and Blue-winged Teal females, which nest later than Mallard, gained weight after spring arrival, lost weight from the onset of nesting until early July, and then regained some weight. Females of all species captured on nests were lighter than those captured off nests at the same time. Male Mallard weights decreased from spring arrival until late May. Male Gadwall and Blue-winged Teal weights increased after spring arrival, then declined until early June. Males of all three species then gained weight until the end of June. Among adults, female Gadwall and male Mallard and Blue-winged Teal were heavier in years when wetland area had increased from the previous year; female Blue-winged Teal were heavier in years with more wetland area.